Inspecting the Cause & Thereby Managing Implant Failure in Dentistry - Kajal Kiran Sahoo; Sudipta Sahu; Debashruti Naik; Nikita Sahu (Indian Journal of Forensic Medicine & Toxicology, 2021)
Dental implants are becoming the most popular mode of treatment nowadays, both partially and fullyedentulous patients. Although several meta-analyses show 93% survival rates of dental implants, failures indental implants are also seen. This review article aims to identify the failing implants at its earliest, makingawareness among the dentists to identify the causes of the failure and thereafter the treatment modalities tomanage such cases.